A Ranking Method Based on Handicaps - Gabrielle Demange (Center for Economic Studies and ifo Institute (CESifo), 2014)
Ranking methods are fundamental tools in many areas. Popular methods aggregate the statements of experts' in different ways. As such, there are various reasonable ranking methods, each one of them more or less adapted to the environment under consideration. This paper introduces a new method, called the handicap-based method, and characterizes it through appealing properties. This method assigns not only scores to the items but also weights to the experts. Scores and weights form an equilibrium for a relationship based on the notion of handicaps. The method is, in a sense made precise in the paper, the counterpart to the counting method in environments that require intensity-invariance. Intensity-invariance is a desirable property when the intensity of the experts' statements has to be controlled. Otherwise, both the counting and handicap-based methods satisfy a property called homogeneity, which is a desirable property when cardinal statements matter, as is the case in many applications. The method is illustrated for ranking economic journals.
Keywords: D71; D89; 330; ranking; scores; invariant method; peers' method; handicap; scaling matrix